2019
DOI: 10.35940/ijrte.b1568.098319
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Resource Allocation for Time-Sensitive IoT Applications in Cloud and Fog Environments

Abstract: Nowadays, with the quick development of internet and cloud technologies, a big number of physical objects are linked to the Internet and every day, more objects are connected to the Internet. It provides great benefits that lead to a significant improvement in the quality of our daily life. Examples include: Smart City, Smart Homes, Autonomous Driving Cars or Airplanes and Health Monitoring Systems. On the other hand, Cloud Computing provides to the IoT systems a series of services such as data computing, proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Comparative analysis has been accumulated and presented in table (6,7,8) given. Table6 shows the, Average Waiting Time of each algorithm (FCFS, SJF and Round Robin) along with different number of processing elements (pesNumber) given in the table.Table7 shows the Average Turnaround Time of each algorithm (FCFS, SJF and Round Robin) along with different number of processing elements (pesNumber).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis has been accumulated and presented in table (6,7,8) given. Table6 shows the, Average Waiting Time of each algorithm (FCFS, SJF and Round Robin) along with different number of processing elements (pesNumber) given in the table.Table7 shows the Average Turnaround Time of each algorithm (FCFS, SJF and Round Robin) along with different number of processing elements (pesNumber).…”
Section: Resultsmentioning
confidence: 99%
“…In article [6], In terms of time delays and response times, the comparison between fog and cloud computing. The performance of fog computing is superior to cloud computing, as long as the delay and response times are reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, an integrated edge-fog-cloud architecture offers scalable data analytics and trustworthy solutions to overcome IoMT application challenges (e.g., the problem of reducing service execution time and energy consumption of IoMT applications) [13]. A number of studies in the literature [10,11,[14][15][16] have highlighted the importance of edge, fog, and cloud computing in terms of optimizing the placement of IoMT applications, considering several performance metrics such as energy consumption, service latency, resource usage, and security [17,18]. This section presents some of the related work for the placement of IoMT applications in edge-fog-cloud systems.…”
Section: Related Workmentioning
confidence: 99%
“…In [15], the authors developed an optimization conceptual fog computing framework that could reduce network communication delays and enhance fog resource utilization via the application of a genetic algorithm. To achieve better performance, authors in [11] conducted a simulation analysis for integrating fog computing with cloud computing paradigms. They found that offloading IoMT data to fog computing reduced response time by approximately 86% compared to the cloud layer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation